Influence of the North American dipole on the Atlantic warm pool - Chao, Jinghua; Fan, Guangzhou; Ding, Ruiqiang; Zhong, Quanjia; Wen, Tao (Frontiers in Earth Science, 2023)
The Atlantic warm pool (AWP) of water having a temperature above 28.5°C encompasses the Gulf of Mexico, the Caribbean, and the western tropical North Atlantic (TNA), influencing the regional and global climate. Much of the AWP interannual variability has been thought to be an outcome of external remote forcing by climate variability outside the tropical Atlantic, such as the El Niño-Southern Oscillation (ENSO) or the North Atlantic Oscillation (NAO). This study indicates that the North American dipole (NAD), exemplified by a north-south seesaw in sea level pressure anomalies over the western TNA and northeastern North America, may provide another integral remote forcing source to influence the AWP. Both observational and model data prove that a strong positive (negative) phase of the winter NAD tends to inhibit (favor) the development of AWP in its area and depth in subsequent months. As opposed to the NAO, the NAD plays a more pivotal role in influencing the AWP due to its effectiveness in forcing the TNA SST variability, which means that AWP variability may be more of a lagging response to NAD atmospheric forcing than a lagging response to NAO atmospheric forcing. Additional analysis indicates that the winter NAD-like atmospheric signal may be stored in the following AWP, thus markedly influencing the TNA precipitation and air temperature in summer. It is speculated that the AWP may act as a bridge linking winter NAD to the following summer precipitation and air temperature in the TNA region.